The Lonely Crowd and the Economic Man - Levitt, Theodore (Quarterly Journal of Economics, 1956)
I. Introduction, 95. — II. Riesman's thesis, 98. — III. Methodological and personal observations, 102. — IV. What is the future of American capitalism with the emergence of the other-directed man? 105. — V. Five significant developments of our other-directed society, 110. — VI. Summary, 116.